A novel deproteinization method from crude polysaccharides of Meretrix meretrix Linnaeus based on palygorskite‐chitosan composite aerogel sieving effect - Yong Zhu; Jingrui Ma; Xinhang Li; Quanrun He; Bingmin Wu; Juanjuan Cheng; Song Huang; Jihang Chen (eFood)
Abstract Due to the delicious taste and remarkable bioactivities of Meretrix meretrix L., they have garnered attention in food field. However, the challenge arises when attempting to separate proteins from crude polysaccharides with similar polarity and solubility. This paper aimed to develop a novel deproteinization method from crude polysaccharides of Meretrix meretrix L. (CPM) based on palygorskite‐chitosan composite aerogel (Pal‐CS aerogel) sieving effect. We focused on the influence of aerogels' pore structure on the selective deproteinization of CPM. In comparison to palygorskite or chitosan, Pal‐CS aerogel exhibited a superior advantage in selectively deproteinization due to its unique pore structure. Furthermore, under the concentration conditions of 2% Pal and 0.8% CS, the deproteinization rate (Dr%), polysaccharide adsorption rate (Pr%) and selectivity coefficient (Kc) reached impressive values of 95.08 ± 1.47%, 3.29 ± 0.14% and 28.95 ± 0.82, respectively. The findings from pore size analysis revealed that an appropriate size ranging from 0.1 μm to 3.0 μm significantly contributed to the selectively deproteinization based on the sieving effect. The adsorption mechanism study further highlighted that hydrogen bonding predominantly dominated the interfacial interaction between aerogel and proteins. In conclusion, this work provided a new perspective for the study on deproteinization of food polysaccharides.